2021
DOI: 10.3390/diagnostics11091622
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Nasopharyngeal Microbiota Profile in Aged Patients with COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) is an infectious virus that causes coronavirus disease 2019 (COVID-19) transmitted mainly through droplets and aerosol affecting the respiratory tract and lungs. Little is known regarding why some individuals are more susceptible than others and develop severe symptoms. In this study, we analyzed the nasopharyngeal microbiota profile of aged patients with COVID-19 (asymptomatic vs. symptomatic) vs. healthy individuals. We examined the nasopharynx swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Delta variant was more contagious, highly transmissible, and virulent than the original strain of the Wuhan virus [ 4 ]. The dysbiosis in healthy microflora of the nasopharyngeal microbiome due to the SARS-CoV-2 infections might be the key driver of the severe infection [ 29 , 30 ]. For example, microbiota composition of the upper respiratory track is associated with the viral load in COVID-19 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delta variant was more contagious, highly transmissible, and virulent than the original strain of the Wuhan virus [ 4 ]. The dysbiosis in healthy microflora of the nasopharyngeal microbiome due to the SARS-CoV-2 infections might be the key driver of the severe infection [ 29 , 30 ]. For example, microbiota composition of the upper respiratory track is associated with the viral load in COVID-19 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…While an important part of the research in this field, especially at the initial moments of the COVID-19 pandemic, has focused mainly on comparing the nasopharyngeal microbiota of SARS-CoV-2 positive individuals to uninfected controls independently on the symptomatology of those patients or the severity of their disease [ 44-49 , 51 , 52 , 57-63 ], many of the most recent studies have gone further and have examined the possible association between the nasopharyngeal microbiota and the COVID-19 disease severity or outcome (Table S1) [ 50 , 53-56 , 64-70 ]. The publications which only compared the nasopharyngeal microbiota composition of asymptomatic or paucisymptomatic SARS-CoV-2 positive subjects to negative healthy controls generally found little or no differences (Table S1) [ 44 , 63 , 65 ].…”
Section: Changes In the Nasopharyngeal Microbiota Of Sars-cov-2-infec...mentioning
confidence: 99%
“…On the other hand, consistent with these results, the work by Bai and colleagues, which included 37 critically ill COVID-19 patients and 20 uninfected controls, showed a reduction in commensal bacteria and higher abundance of pathogenic bacteria in patients compared to healthy uninfected controls (Table S1) [ 52 ]. But even more interesting are the approaches analyzing the nasopharyngeal microbiota composition of COVID-19 patients with different levels of disease severity within the same study, since most of these works observed significant differences when comparing symptomatic subjects to asymptomatic/paucisymptomatic individuals and/or uninfected controls (Table S1) [ 46 , 50 , 54-56 , 64-66 , 68-70 ]. Among the studies belonging to this group, Nardelli and colleagues, who were the first authors to select a homogeneous group of COVID-19 patients sharing that all of them were symptomatic, revealed that Proteobacteria and Fusobacteria relative abundances decreased in symptomatic COVID-19 patients compared to uninfected controls, particularly the genera Leptotrichia , Haemophilus , and Fusobacterium (Table S1) [ 46 ].…”
Section: Changes In the Nasopharyngeal Microbiota Of Sars-cov-2-infec...mentioning
confidence: 99%
“…oral commensals similar to those found in the oropharynx, such as Streptococcus, Prevotella, and Veillonella. A major confounding factor for many nasopharyngeal studies was the storage of samples in viral transport media, as many studies looked at the microbiome using swabs that were initially collected for viral testing or sequencing [55][56][57][58].…”
Section: Inconsistent Analytical Techniquesmentioning
confidence: 99%